Female Sexual Dysfunction in Women with Pelvic Pain - Tam, Teresa; Levine, Elliot M. (Seminars in Reproductive Medicine, 2018)
A variety of conditions can give rise to the perception of painful sexual intercourse in women with pelvic pain. Female sexual dysfunction may stem from psychological, medical such as endocrinological disturbances, and gynecological pathologies. This article provides a discussion of various conditions, offering diagnostic and therapeutic measures to consider in women with pelvic pain experiencing sexual dysfunction. Treatment and management options are also reviewed.
Keywords: sexual dysfunction; pelvic pain; painful sex; female sexual dysfunction